THE ROLE OF LEADERSHIP, COMPETENCE AND WORK MOTIVATION IN IMPROVING EMPLOYEE PERFORMANCE AT THE DEPARTMENT IN SOUTHWEST PAPUA - Ferry Anggro; Vebby Anwar; Mervin Irian Sadipun Komber (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2026)
This study analyzes the influence of leadership and competence on employee performance, with work motivation as an intervening variable at the Department of Manpower, Transmigration, Energy, and Mineral Resources of Southwest Papua Province. The study utilizes a quantitative methodology, involving 43 civil servants chosen via purposive sampling. Data were collected using questionnaires and analyzed by multiple linear regression, path analysis, and the Sobel test. The findings indicate that leadership and competence significantly affect both work motivation and employee performance. Furthermore, work motivation is proven to significantly mediate the influence of leadership and competence on employee performance. These findings underscore the necessity of enhancing leadership quality, augmenting employee competence, and fortifying work motivation to elevate employee performance within regional government agencies. The practical implication of this research provides a reference for formulating effective human resource management policies in the public sector.